Veterans : Pensions and Other Compensation in Post-Conflict Countries - World Bank (Washington, DC, 2012)
The question of how best to compensate veterans in the aftermath of war is one that is relevant to many developing countries. Civil wars and independence struggles often affect the poorest regions of the world, and leave an enormous financial burden, including benefits to former fighters and their survivors. The most recent examples are Afghanistan and Iraq. One of the many challenges post-conflict countries face is how to reduce the size of armies once the fighting stops, and how to assist former fighters or veterans, in a sustainable manner once they are no longer part of the army. Fiscal, social, or political pressures may all play a role in this process, including in peace-time. This note attempts to provide the reader with an overview of the different dimensions of veterans policy development, with particular reference to countries emerging from protracted conflict. Special attention is given to the common problems of definition, inclusion, financial sustainability and implementation, as well as the linkages between disarmament, demobilization and reintegration (DDR) and veterans policy.